Patterns, causes, and clinical impact of treatment interruption on early outcomes in patients receiving radiotherapy for lung cancer: a retrospective study - Lifa Su; Longbin Zhang; Qiang Liu; Xin He; Xiaoqing Luo (Frontiers in Oncology, 2026)
Background Radiation therapy is key for lung cancer, but data on unplanned interruptions remains limited. Objectives This study investigated patterns, risk factors, and clinical impacts of radiotherapy interruptions in lung cancer patients. Methods A retrospective study enrolled 230 lung cancer patients undergoing radiotherapy (Jan 2020‐Dec 2022). After exclusion, 226 patients were analyzed and stratified into interrupted and non-interrupted groups by unplanned radiotherapy interruptions (≥1-day pause, excluding scheduled breaks). Patterns and causes of interruptions were documented in detail. Early oncological response, treatment completion, acute toxicities, progression-free survival (PFS), and overall survival (OS) were monitored at 6 months post-radiotherapy. Multivariable linear regression identified interruption risk factors, while Cox regression and Kaplan–Meier analysis with log-rank test evaluated survival. Results A total of 226 lung cancer patients were enrolled, 79 (34.96%) of whom had at least one treatment interruption, with a median duration of 5 days and 1 episode. Most interruptions occurred in the middle third of radiotherapy (60.76%), mainly caused by treatment-related toxicities (49.37%) and patient-related factors (27.85%). Multivariable linear regression showed that performance status (PS) score 2–3, stage III–IV and tumor volume ≥50 cm³ remained significantly associated with radiotherapy interruption after adjustment for potential confounders (all P<0.05). The interrupted group had poorer compliance, lower overall response rate (ORR) and disease control rate (DCR), higher acute toxicities. Unadjusted Kaplan-Meier analysis showed worse 6-month PFS and OS in the interrupted group, and this association persisted in multivariable-adjusted Cox regression after controlling for PS score, tumor stage, tumor volume, treatment regimen, and radiotherapy modality (all P < 0.001). Conclusions Radiotherapy interruption is common in lung cancer patients, mainly caused by toxicity. It impairs treatment efficacy and survival, requiring individualized management.